2020
DOI: 10.1111/desc.12960
|View full text |Cite
|
Sign up to set email alerts
|

One language or two? Navigating cross‐language conflict in statistical word segmentation

Abstract: Despite the prevalence of bilingualism (Crystal, 2004; Grosjean, 2010), there is limited work investigating how infants detect words in two languages. Infants with bilingual exposure may encounter conflicting prosodic, lexical, and co-occurrence cues to word boundaries across their languages, which in turn could disrupt word segmentation. For example, an infant learning both French and English would encounter opposing prosodic cues; the predominant stress pattern in English is trochaic (strong-weak), whereas F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
3
6
0
Order By: Relevance
“…The authors found that 8‐month‐old monolingual infants exhibited no evidence of learning sequentially presented artificial languages when they contained overlapping syllables that formed different words in each language, but infants could learn the languages when presented separately. This finding aligns with Antovich and Graf Estes' finding (2020) that monolingual infants failed to demonstrate learning of interspersed artificial languages that contained conflicting syllable patterns. As a whole, these lines of work suggest that infants' learning of sound sequences can interact across speech streams.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…The authors found that 8‐month‐old monolingual infants exhibited no evidence of learning sequentially presented artificial languages when they contained overlapping syllables that formed different words in each language, but infants could learn the languages when presented separately. This finding aligns with Antovich and Graf Estes' finding (2020) that monolingual infants failed to demonstrate learning of interspersed artificial languages that contained conflicting syllable patterns. As a whole, these lines of work suggest that infants' learning of sound sequences can interact across speech streams.…”
Section: Introductionsupporting
confidence: 91%
“…This aligns with the work from Lany et al. (2018) and Antovich and Graf Estes (2020), who found associations between laboratory statistical learning tasks and language processing in 15‐month‐olds and between statistical learning and bilingual input in 16‐month‐olds, respectively. These connections suggest that even early in development, there is a relationship between lab‐based statistical learning tasks and real‐world language processing abilities.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…A recent analysis suggests that bilingual infants exposed to more frequent language mixing (including within-sentence switching) are more successful in segmenting words out of both of their languages (Orena & Polka, 2019). Moreover, monolinguals presented with a “bilingual” input in an artificial language setting failed to segment words from those languages (Antovich & Graf Estes, 2018, 2020), suggesting that in natural language acquisition, infants may lose the capacity to keep track of two sets of cues if exposed to a predominantly consistent input; or perhaps that multilinguals gain the capacity to track multiple sets of cues when exposed to variable input (see particularly follow-up analyses on frequency of mixing, in Orena & Polka, 2019; and on proportion of bilingual speakers in the environment, in Antovich & Graf Estes, 2020). Although many of these studies report significant preferences, it should be noted that the direction of preference is sometimes toward familiarity (as in most previous word segmentation studies on monolinguals) and sometimes towards novelty (i.e., longer looking to the test stimuli with a foil than with the familiarized word).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been studied extensively in infancy (e.g., Aslin, Saffran & Newport, 1998; Pelucchi, Hay & Saffran, 2009; a review in Lany & Saffran, 2010; Saffran, Aslin & Newport, 1996), often (but not always) using artificial languages where all other cues (including phrase breaks) have been neutralised (a meta-analysis in Black & Bergmann, 2017). Importantly, these cues are also employed by bilingual infants: who can keep track of two sets of statistics presented in interleaved utterances better than monolingual infants (Antovich & Graf Estes, 2018, 2020).…”
Section: Introductionmentioning
confidence: 99%